A conservation roadmap for the subterranean biome. Issue 5 (13th August 2021) - Wynne, J. Judson; Howarth, Francis G.; Mammola, Stefano; Ferreira, Rodrigo Lopes; Cardoso, Pedro; Lorenzo, Tiziana Di; Galassi, Diana M. P.; Medellin, Rodrigo A.; Miller, Bruce W.; Sánchez‐Fernández, David; Bichuette, Maria Elina; Biswas, Jayant; et al.
Abstract: The 15th UN Convention on Biological Diversity (CBD) (COP15) will be held in Kunming, China in October 2021. Historically, CBDs and other multilateral treaties have either alluded to or entirely overlooked the subterranean biome. A multilateral effort to robustly examine, monitor, and incorporate the subterranean biome into future conservation targets will enable the CBD to further improve the ecological effectiveness of protected areas by including groundwater resources, subterranean ecosystem services, and the profoundly endemic subsurface biodiversity. To this end, we proffer a conservation roadmap that embodies five conceptual areas: (1) science gaps and data management needs; (2) anthropogenic stressors; (3) socioeconomic analysis and conflict resolution; (4) environmental education; and (5) national policies and multilateral agreements.